Pengaruh Electronic Word of Mouth dan Product Quality Terhadap Purchase Decision Dengan Brand Image Sebagai Variabel Mediasi (Studi produk Ortuseight di Kalimantan Barat) - Shandy, Jose Haris; A, Ahmadi; Listiana, Erna; Fitriana, Ana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The sports shoe market in Indonesia is expected to experience rapid growth in the next few years. This growth is driven by changes in people’s lifestyles that increasingly prioritize health and physical activity, increasingly popular sports trends, and the ease of purchasing products through e-commerce. Amidst this market growth, local sports shoe brand Ortuseight has succeeded in taking advantage of the trend by offering high-quality products that suit an active lifestyle. The interaction between product quality, EWOM, and brand image in influencing purchasing decisions, this study aims to explore how these three variables are interrelated in the sports shoe market. This study will also assess how brand image as a moderating variable can strengthen or reduce the influence of EWOM and product quality on purchasing decisions for Ortuseight shoes with a sample of 160 respondents. Respondents who have purchased Ortuseight products at least once in the last 6 months because they see information, especially platforms that are popular among young users such as Instagram and TikTok. The data collection method uses a questionnaire through a purposive sampling technique with a quantitative approach. The hypothesis built in this study will be tested with a causal design approach. The test tool used to see the relationship between independent and dependent variables uses Structural Equation Modeling (SEM) with statistical tools SmartPLS software version 4. The results of this study found that EWOM and Product Quality have an effect on Purchase Decision with Brand Image which also has a positive effect as a mediating variable. Ortuseight is advised to be more active in managing digital interactions with consumers, especially through social media and local sports communities, in order to encourage the spread of positive reviews organically.